2021
DOI: 10.3855/jidc.15157
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of tigecycline-resistant Klebsiella pneumoniae ST11 clone in patients without exposure to tigecycline

Abstract: Introduction: Tigecycline is a unique class of semi-synthetic glycylcyclines developed to treat infections caused by multidrug-resistant Klebsiella pneumoniae. In the past decades, eight tigecycline-resistant Acinetobacter baumannii isolates have been identified in Tehran and no Klebsiella pneumoniae has been reported. Methodology: To elucidate the mechanism of K. pneumoniae efflux pump-mediated resistance, the expression of efflux pump genes (oqxA, oqxB, acrA, acrB, tolC) and regulators (acrR, ramA, mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Studies have shown that high doses of tigecycline, such as 100 mg every 12 hours, are more effective in treating multidrug-resistant gram-negative bacteria, and that lower doses may not only be insufficient to treat bacterial infections but also increase antibiotic pressure leading to the growth of dominant flora ( Zhou et al., 2021 ). Of concern is the gradual emergence of tigecycline-resistant K. pneumoniae and A. baumannii due to the widespread use of tigecycline, which undoubtedly increases the challenge of antibiotic therapy, making optimization of tigecycline treatment regimens urgent for clinicians ( Goodarzi et al., 2021 ; Sun et al., 2022 ). We also focused on the differences in blood tests between the three groups, the results of host immune indicators indicate that the co-infection response is mainly countered by neutrophils, which have no effect on T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that high doses of tigecycline, such as 100 mg every 12 hours, are more effective in treating multidrug-resistant gram-negative bacteria, and that lower doses may not only be insufficient to treat bacterial infections but also increase antibiotic pressure leading to the growth of dominant flora ( Zhou et al., 2021 ). Of concern is the gradual emergence of tigecycline-resistant K. pneumoniae and A. baumannii due to the widespread use of tigecycline, which undoubtedly increases the challenge of antibiotic therapy, making optimization of tigecycline treatment regimens urgent for clinicians ( Goodarzi et al., 2021 ; Sun et al., 2022 ). We also focused on the differences in blood tests between the three groups, the results of host immune indicators indicate that the co-infection response is mainly countered by neutrophils, which have no effect on T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Kingdom and the United States (Goodarzi et al, 2021). Interestingly, a tigecycline-resistant Acinetobacter baumannii strain was isolated in Iran, but tigecycline was not approved in this country at that time (Goodarzi et al, 2021).…”
Section: Mechanisms Of Tigecycline-resistancementioning
confidence: 99%
“…The incidence of tigecycline resistance has been increasing yearly since 2007 ( Sun et al., 2013 ). In recent decades, many strains of tigecycline-resistant pathogens have been reported in France, Germany, Greece, Saudi Arabia, Spain, Taiwan, the United Kingdom and the United States ( Goodarzi et al., 2021 ). Interestingly, a tigecycline-resistant Acinetobacter baumannii strain was isolated in Iran, but tigecycline was not approved in this country at that time ( Goodarzi et al., 2021 ).…”
Section: Mechanisms Of Tigecycline-resistancementioning
confidence: 99%
See 2 more Smart Citations